Planning and Creating a Government Web Site: Learning from the Experience of US States - LINDA DeCONTI (Working Paper Series Paper No. 2, 1998)
This paper reviews the history and explosive growth of Internet use and, in particular, the development of the World Wide Web, which has attracted millions of users. It identifies the significant external factors - such as telecommunications infrastructure and government legislation - that will impact the development of this medium in the future. The advent of these new technologies coincides with increasing demands for public access to government information. The tools of the Internet provide a vehicle for improved information sharing among branches of government as well as with the public. The paper describes the different stakeholder groups who may be involved with and affected by this process. Many governments have created, or are seeking to create, a Web presence. A set of information delivery principles and Web site design criteria are therefore presented. These criteria are then used to evaluate the Web sites of forty-eight US State governments, providing insights into both best and worst practice for government. The paper concludes with some details of the strategic approaches to Web site development that governments may need to adopt.